Editors' Introduction to the Special Issue on ‟Applications in Information Technology” - Pyshkin, Evgeny; Klyuev, Vitaly; Vazhenin, Alexander P. (Informatica, 2017)
Editors' Introduction to the Special Issue on ‟Applications in Information Technology”